Ч. 3 : Руководство к самостоятельной проектной работе студентов; Физика - Поздеева Э. В. Эльвира Вадимовна; Склярова Е. А. Елена Александровна; Ларионов В. В. Виталий Васильевич (2015, 2015)
Заглавие с титульного экрана